Membaca Radikalisme Semu di Komisi Pemberantasan Korupsi (KPK): Analisis Wacana Isu Taliban pada Tubuh KPK - Hanna Nurhaqiqi (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2021)
The case of the failure of 75 KPK employees is claimed to have something to do with radicalism within the KPK. Through this discourse analysis of news texts, a study of the meaning of the news texts of Koran Tempo and Republika is carried out to determine the structure of the news text, social cognition and social context. The results found are Koran Tempo and Republika, with different media ideologies, have an intersecting discourse structure where they both assume that radicalism related to the failure of 75 KPK employees has no facts. There needs to be clarity from the TWK test preparation of government agency.